Contributions of HFE polymorphisms to brain and blood iron load, and their links to cognitive and motor function in healthy adults. Issue 3 (21st July 2021) - Kalpouzos, Grégoria; Mangialasche, Francesca; Falahati, Farshad; Laukka, Erika J; Papenberg, Goran
Abstract: Background: Brain iron overload is linked to brain deterioration, and cognitive and motor impairment in neurodegenerative disorders and normal aging. Mutations in the HFE gene are associated with iron dyshomeostasis and are risk factors for peripheral iron overload. However, links to brain iron load and cognition are less consistent and data are scarce. Aims and methods: Using quantitative susceptibility mapping with magnetic resonance imaging, we investigated whether C282Y and H63D contributed to aging‐related increases in brain iron load and lower cognitive and motor performance in 208 healthy individuals aged 20‐79 years. We also assessed the modulatory effects of HFE mutations on associations between performance and brain iron load, as well as peripheral iron metabolism. Results: Independent of age, carriers of either C282Y and/or H63D ( HFE ‐pos group, n = 66) showed a higher load of iron in putamen than non‐carriers ( HFE ‐neg group, n = 142), as well as higher transferrin saturation and lower transferrin and transferrin receptors in blood. In the HFE ‐neg group, higher putaminal iron was associated with lower working memory. In the HFE ‐pos group, higher putaminal iron was instead linked to higher executive function, and lower plasma transferrin was related to higher episodic memory. Iron‐performance associations were modest albeit reliable. Conclusion: Our findings suggest that HFE status is characterized by higher regional brain iron load across adulthood, and support the presence of a modulatory effect of HFE status on the relationships between iron load and cognition. Future studies in healthy individuals are needed to confirm the reported patterns. Abstract : This study investigated the contribution of genetic polymorphisms in the HFE gene (C282Y and H63D) on blood and brain iron load, and their relationships with cognition, in a healthy sample of adults. The findings indicated that carriers of C282Y and/or H63D displayed higher iron load in putamen and higher transferrin saturation in blood. Results further suggested that in carriers, higher iron load may be beneficial for cognitive performance, independent of age.